2013
DOI: 10.1002/mma.2988
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a predator–prey model with disease in the predator

Abstract: The present investigation deals with a predator-prey model with disease that spreads among the predator species only. The predator species is split out into two groups-the susceptible predator and the infected predator both of which feeds on prey species. The stability and bifurcation analyses are carried out and discussed at length. On the basis of the normal form theory and center manifold reduction, the explicit formulae are derived to determine stability and direction of Hopf bifurcating periodic solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Hilker and Schmitz [12] observed that introducing disease into the Rosenzweig- MacArthur model can stabilize prey-predator oscillations. Some studies have been carried out on eco-epidemiological models with disease either in prey [13][14][15][16] or in predator [17][18][19][20] or in both populations [21][22][23]. The infectious diseases among prey and predator populations are disorders caused by bacteria or virus [24].…”
Section: Introductionmentioning
confidence: 99%
“…Hilker and Schmitz [12] observed that introducing disease into the Rosenzweig- MacArthur model can stabilize prey-predator oscillations. Some studies have been carried out on eco-epidemiological models with disease either in prey [13][14][15][16] or in predator [17][18][19][20] or in both populations [21][22][23]. The infectious diseases among prey and predator populations are disorders caused by bacteria or virus [24].…”
Section: Introductionmentioning
confidence: 99%
“…Further articles have been done also in the field of epidemiology. In fact, recently, there is increasing interest from the scientists by combining ecology and epidemiology in one field that is called ecoepidemiology, which has become a major field of study, see, for example, [21][22][23][24] and the references therein. Recently, Wang et al [25] proposed and studied a generalized ecoepidemiological system with prey refuge.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that infection in the predator species may save the prey from death even if the basic reproduction number was less than one, for which the prey to be able to occupy the predator. Pal et al (2014) gave a predator-prey model with disease in predator species only. They showed that for some values of the predation rate all species could be survived and the disease did not transmit in the predator population.…”
Section: Introductionmentioning
confidence: 99%